Financial Planning Analysis of an E-Commerce Platform Business for Car Spare Parts: a Case Study of PT Fita Auto Nusantara - D. Rio Ardi Perdana; Rhian Indradewa; Dimas Angga Negoro; Mira Kartika Dewi Djunaedi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the financial plan within the business plan for establishing PT Fita Auto Nusantara, a company operating the PartGenie e-commerce platform for the online sale of genuine car spare parts in Indonesia. The analysis focuses on five stages of financial planning: setting financial goals and targets, planning financial elements (revenue, costs, investment, capital requirements, and financing), preparing ten year financial statement projections (income statement, balance sheet, and cash flow), investment feasibility analysis using Return on Investment (ROI), Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PP), and financial performance analysis through liquidity, solvency, profitability, and activity ratios. The method used is a descriptive quantitative method based on document study of the financial projection data compiled in the PartGenie business plan document. The results show that the initial capital requirement of Rp16,000,000,000, sourced 50% from shareholders' equity and 50% from a shareholder loan, is deemed feasible, with a positive NPV of Rp24,483,775,713, an IRR of 24% exceeding the discount rate (WACC) of 11.50%, and a Payback Period of 6.41 years. The company is projected to incur losses in the first three years of operation before achieving positive net income in the third year, with significant profit growth and improved profitability ratios from the fifth year onward. However, the solvency ratio analysis indicates a period of unstable capital structure in the early years that warrants management attention. This study provides empirical insight into the financial feasibility of the digital automotive spare part platform business model in Indonesia.